2016
DOI: 10.32677/ijch.2016.v03.i03.003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of invasive candidal infection in very low birth weight neonates over a period of 5-year: A single institutional study

Abstract: Background: Fungal infection is one of the important causes of bloodstream infection in very low birth weight (VLBW) and extremely low birth weight (ELBW) infants. Objective: To find out the incidence, mortality rate, and clinical spectrum of infants with invasive candidal infection (ICI) among VLBW infants. Materials and Methods: A retrospective descriptive study was conducted over a period of 5-year at a tertiary care hospital. VLBW infants admitted within 24 h of birth were included. The clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Failure to thrive (18/30) and lethargy (15/30) were consistent clinical findings in our neonatal cases, similar to other studies. 17,18,6,19 Respiratory distress (74.55%) followed by failure to thrive and lethargy were most common clinical findings in a study by Sardana et al whereas Juyal et al showed failure to thrive (74.42%) followed by abdominal distension and feed intolerance. 13,16 Candida species are an increasingly common cause of neonatal sepsis and are responsible for considerable morbidity and mortality.…”
Section: Failure To Thrive Lethargy Respiratory Distress Feed Intolermentioning
confidence: 97%
“…Failure to thrive (18/30) and lethargy (15/30) were consistent clinical findings in our neonatal cases, similar to other studies. 17,18,6,19 Respiratory distress (74.55%) followed by failure to thrive and lethargy were most common clinical findings in a study by Sardana et al whereas Juyal et al showed failure to thrive (74.42%) followed by abdominal distension and feed intolerance. 13,16 Candida species are an increasingly common cause of neonatal sepsis and are responsible for considerable morbidity and mortality.…”
Section: Failure To Thrive Lethargy Respiratory Distress Feed Intolermentioning
confidence: 97%